2022
DOI: 10.1007/s11916-022-01086-y
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID Headache: A Literature Review

Abstract: Purpose of Review Post-COVID headache may be unique in presentation and mechanism, often presenting as a new phenotype in patients with a history of a primary headache disorder or resulting in a new headache syndrome in those without history of headache. This review presents a description of the literature published focused on post-COVID headache. Additionally, we discuss potential mechanisms and considerations for treatment of post-COVID headache. Recent Findings Heada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
5
0
4
Order By: Relevance
“…The other point related to the physical condition that explains the slowing in reaction times was the presence of a headache. Headaches and migraines are a well-known consequence of COVID-19 and one of the main symptoms of long-COVID [66]. Most participants in our study reported headaches, ranging in severity from mild to severe.…”
Section: Discussionmentioning
confidence: 58%
“…The other point related to the physical condition that explains the slowing in reaction times was the presence of a headache. Headaches and migraines are a well-known consequence of COVID-19 and one of the main symptoms of long-COVID [66]. Most participants in our study reported headaches, ranging in severity from mild to severe.…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, post-viral cephalea is attributed to the direct invasion of the virus into the central nervous system through retrograde axonal transport, primarily via the olfactory nerve. This type of headache manifests in various phenotypes, and treatment should be tailored to each specific presentation [ 129 ].…”
Section: Neurological Manifestations and Complicationsmentioning
confidence: 99%
“…Similarly, there are no controlled clinical trials specifically examining the efficacy of treatments for post‐COVID headaches. It is currently recommended to identify the pain pattern of headache presented by the patient (migraine vs. tension‐type headache phenotype) and to treat it according to this pattern (Chhabra et al, 2022; Sampaio Rocha‐Filho, 2002). Some preventive drugs used for other chronic headaches might be effective, but so far there are few publications on this topic.…”
Section: Current Management Of Long‐covidmentioning
confidence: 99%